2018
DOI: 10.1097/md.0000000000011529
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy can ameliorate the EMT phenomenon in keloid tissue

Abstract: Background:Hyperbaric oxygen therapy (HBOT) has been widely used in the clinical setting. In this study, HBOT therapy was evaluated for its ability to ameliorate the epithelial-to-mesenchymal transition (EMT) phenomenon in keloid tissue.Methods:Keloid patients were randomly divided into two groups: keloid patients (K group, 9 patients) and keloid patients receiving HBOT (O group, 9 patients). A third group with normal skin (S group, 9 patients) was established for control. Before HBOT and surgery, a laser Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
(48 reference statements)
0
16
0
3
Order By: Relevance
“…[ 12 ] The molecular biologic effects of HBOT on keloids were also studied. Zhang et al [ 11 ] found that HBOT can ameliorate the keloid EMT process by influencing hypoxia inducible factor-1α(HIF-1α) expression. In addition, HBOT can also influence the expression of inflammatory factors, such as IL-12p40, macrophage inflammatory protein-1β(MIP-1β), Platelet derived growth factor (PDGF-BB), and IL-1R.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] The molecular biologic effects of HBOT on keloids were also studied. Zhang et al [ 11 ] found that HBOT can ameliorate the keloid EMT process by influencing hypoxia inducible factor-1α(HIF-1α) expression. In addition, HBOT can also influence the expression of inflammatory factors, such as IL-12p40, macrophage inflammatory protein-1β(MIP-1β), Platelet derived growth factor (PDGF-BB), and IL-1R.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH, glyceraldehyde 3-phosphate dehydrogenase; lncRNA, long-chain noncoding RNA; miR-29a, microRNA-29a miRNAs has been documented to express aberrantly during TGF-β-stimulated EMT, 35 which was a featured phenomenon of keloid onset. 36 For example, the miR-200 family and miR-205 modified EMT of breast cancer through prohibiting expression of ZEB, and enforced downregulation of miR-200 expression could bring down E-cadherin expression evidently. 37 Within this investigation, we found that miR-29a expression in fibroblasts declined after being sponged by H19 (Figure 4), just as in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…A oxigenoterapia hiperbárica -OHBé caracterizada por exposição a 100% de oxigênio ambiente, sendo muito usada em lesões de difícil cicatrização, algumas doenças do sistema nervoso central e diminuir a incidência de inflamações. Além disso, a terapia induz a redução da expressão de HIF1-alfa, interleucina1Beta e fator de necrose tumoral (TNF) (ZHANG et al, 2018). Diante disso, ZHANG et al ( 2018) desenvolveu uma pesquisa clínica com 27 pacientes portadores de queloide e não queloide, escolhidos aleatoriamente.…”
Section: Resultsunclassified
“…Geralmente atinge apenas a derma, exceto na síndrome de Lowe a qual acomete tecidos epiteliais da córnea (HOCHMAN et al, 2004;ZHANG et al, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation